2020
DOI: 10.1093/abm/kaaa060
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Edged Sword of Reflective Pondering: The Role of State and Trait Reflective Pondering in Predicting Depressive Symptoms Among Women With Breast Cancer

Abstract: Background and Purpose Prior research has debated whether reflective pondering is a more constructive form of rumination than brooding, which is generally considered maladaptive. This study sought to investigate whether reflective pondering predicts depressive symptoms and whether reflective pondering is adaptive under certain conditions. We predicted that the effectiveness of reflective pondering could depend on concurrent coping strategies and the trait–state distinction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Incongruent with findings from previous research, disengagement and engagement coping were not related to depressed affect at 5-year follow-up (Bonnaud-Antignac et al, 2017; Bright & Stanton, 2018; Kim et al, 2020; Kvillemo & Branstrom, 2014; Stanton et al, 2018; A. W. Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Incongruent with findings from previous research, disengagement and engagement coping were not related to depressed affect at 5-year follow-up (Bonnaud-Antignac et al, 2017; Bright & Stanton, 2018; Kim et al, 2020; Kvillemo & Branstrom, 2014; Stanton et al, 2018; A. W. Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…Future longitudinal research should seek to explore whether the current relationships hold in more contemporary samples and after accounting for these additional covariates. Finally, upcoming work should consider using statistical methods that allow for the assessment of coping variability (i.e., latent class analysis; Kim et al, 2020) and/ or control for previous indices of coping to delineate the effect of state versus trait coping responses (A. W. Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that it is useful to distinguish state rumination from trait rumination more precisely in Chinese with this tool and further explore the different functions and neural mechanisms of the two styles of rumination. Some researchers have found that state and trait rumination have different effects on stress and other diseases (17,(57)(58)(59). For instance, state and trait rumination contribute to depression in different ways (58).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found that state and trait rumination have different effects on stress and other diseases (17,(57)(58)(59). For instance, state and trait rumination contribute to depression in different ways (58). Another research study has shown that the interaction of trait and state rumination shapes the HPA-axis response to stress (59).…”
Section: Discussionmentioning
confidence: 99%